PELAKSANAAN PERJANJIAN KERJASAMA INVESTASI ANTARA INVESTOR DENGAN PERUSAHAAN PIALANG BERJANGKA - Galih Mahendratama Putra, Budiharto, Siti Mahmudah (Diponegoro Law Journal, 2012)
In the presence commodity Stock at Indonesian at starts its happening various put-upon case on year 1970 an who is done many going commissioner firm mandate channelizing activity contracts to get commodity meter from client at home affairs goes to Stock get meter beyond seas. Currently trade commodity is managed in Number Law 10 Years 2011 about Commodity future and Number Government regulations 9 Years 1999 about Commodity Future Managements.